Analysis of dog bites institutional data, Savannah Region, Ghana, 2018-2022 - Kwabena Adjei Sarfo; Williams Azumah Abanga; Joseph Alphonsus Chantiwuni Nindow; Wadeyir Jonathan Abesig; Gyesi Razak Isshaku; Magdalene Akos Odikro; George Akowuah; Delia Akosua Benewaa Bando; Ernest Kenu; Chrysantus Kubio (Journal of Interventional Epidemiology and Public Health)
Introduction: Dog bite injuries in humans are still a major public health concern. Dogs are responsible for 76 to 94 percent of animal bite injuries. There have not been enough national reports on dog bite injuries in Ghana, and understanding the current state of the injuries is important for effective interventions. We described dog bite cases in the Savannah Region of Ghana.